Calcium binding to HMG1 protein induces DNA looping by the HMG-box domains - Stros, M; Reich, J; Kolíbalová, A (FEBS letters, 1994)
Electron microscopy has shown that non-histone chromosomal HMG1 could induce DNA looping or compaction in the presence (but not in the absence) of Ca2+. The effect of calcium on DNA looping and compaction was interpreted as calcium binding to the acidic C-domain of HMG1. Both individual DNA-binding HMG1-box domains A and B were found to be involved in DNA looping and compaction. Treatment of HMG1 with a thiol-specific reagent, N-ethylmaleimide, inhibited the ability of the protein to induce DNA looping and compaction but not the electrostatic interaction with DNA. These results indicated that cysteine-sulfhydryl groups of the HMG1-box domains A and B are specifically involved in DNA looping and compaction, and that in the absence of calcium the acidic C-domain down-regulates these effects by modulation of the DNA-binding properties of the HMG1-box domains.
Keywords: Liver; Microscopy, Electron; konformace nukleové kyseliny; Rats; játra; Nucleic Acid Conformation; DNA; High Mobility Group Proteins; Ethylmaleimide; elektronová mikroskopie; rekombinantní proteiny; vápník; skot; krysa rodu Rattus; Calcium; proteiny s vysokou pohyblivostí; zvířata; Binding Sites; Cattle; Thymus Gland; thymus; ethylmaleimid; vazebná místa; Recombinant Proteins; Animals